To solve for b, we start by isolating the b term on one side of the equation.
4a = 2b - 7
First, we add 7 to both sides to get rid of the -7:
4a + 7 = 2b
Next, we divide both sides by 2 to solve for b:
(4a + 7) / 2 = b
Simplifying the expression:
2a + 3.5 = b
Now we have the equation in terms of b.
To find the value of b when a = 3, we substitute a = 3 into the equation:
2(3) + 3.5 = b
Simplifying the expression:
6 + 3.5 = b
Combining like terms:
9.5 = b
So, when a = 3, b = 9.5.
solve for b, then find the value of b when a = 3
4a=2b-7
1 answer